Genetic Diversity of Simpo and Limpo Cattle Based on Five Blood-protein Locus Polymorphism - Lestari, Dela Ayu; Sutopo, Sutopo; Setiaji, Asep; Kurnianto, Edy (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
Simpo and Limpo cattle is a crossbred cattle of Indonesian local cattle and exotic cattle that popular among traditional farmers in Indonesia. The objective of this study was to identify genetic diversity of Simpo and Limpo cattle based on blood-protein polymorphism. A total of 70 blood samples were collected from unrelated 35 heads of Simpo cattle and 35 heads of Limpo cattle from Grobogan dan Kendal population. The blood plasm was used to identify the blood proteins. Blood protein analysis was performed using Sodium Dodecyl Sulfate-Polyacrilamide Gel Electrophoresis (SDS-PAGE). Observed bands were used to perform allele interpretation of five locus, namely Pre-albumin (Pe-Alb), Albumin (Alb), Post-albumin (Po-Alb), Ceruloplasmin (Cp) and Amylase-1 (Am-1). Results showed there were polymorphism in all of the five blood protein locus in both cattle; 4 of 5 and 2 of 5 of the blood-protein locus studied showed deviation from Hardy-Weimberg Equilibrium (HWE) for Simpo and Limpo cattle, respectively and the average heterozygosity value (H) was 0.478 and 0.362 for Simpo and Limpo cattle, respectively. In conclusion, the study indicated that population of Simpo and Limpo cattle has high genetic diversity. Keywords: allele frequency; genotype frequency; heterozygosity